2022
DOI: 10.1039/d2na00429a
|View full text |Cite
|
Sign up to set email alerts
|

The benefits of combining 1D and 3D nanofillers in a piezocomposite nanogenerator for biomechanical energy harvesting

Abstract: Mechanical energy harvesting using piezoelectric nanogenerators (PNGs) offer an attractive solution for driving low-power portable devices and self-powered electronic systems. Here, we designed an eco-friendly and flexible piezocomposite nanogenerator (c-PNG)...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 76 publications
0
3
0
Order By: Relevance
“…Another study by the same group reported a composite thin-film-based PENG composed of HZTO-NW and BCZT as the fillers and PLA as the polymer matrix. 67 A finger touch on the PENG produced an output voltage of 11.5 V, output current of 0.6 mA, and a power density of 9200 mW cm À3 .…”
Section: Ifes and Flexible Energy Harvestersmentioning
confidence: 99%
“…Another study by the same group reported a composite thin-film-based PENG composed of HZTO-NW and BCZT as the fillers and PLA as the polymer matrix. 67 A finger touch on the PENG produced an output voltage of 11.5 V, output current of 0.6 mA, and a power density of 9200 mW cm À3 .…”
Section: Ifes and Flexible Energy Harvestersmentioning
confidence: 99%
“…[48,70] To control or manipulate this homogeneity of additives, researchers have studied the introduction of additives with different dimensionalities into polymer matrices. Hanani et al [71] have demonstrated that the co-addition of both 1D and 3D additives into a polylactic acid matrix led to a significant improvement compared to either 1D or 3D additive individually. The nature of additives and filler matrix are blurred when a complete piezoceramic foam is embedded in a polymer mesh, as described by Zhang et al [72] and Zhang et al [73] These porous systems also can create ferroelectrets giving rise to further enhanced electromechanical response, which will be discussed in subsequent sections.…”
Section: Polymer Composite Materialsmentioning
confidence: 99%
“…Degradable flexible electronics have broad application prospects in nextgeneration wearable devices and implantable bioelectronics. [11][12][13] Wearable flexible electronics often use conductive nanomaterials to provide electrical properties. [14][15][16] Commonly used conductive nanomaterials include carbon nanotubes, 17,18 graphene, 19,20 conductive polymers, [21][22][23][24] and metal nanowires.…”
Section: Introductionmentioning
confidence: 99%
“…The prepared microelectrode has good biocompatibility, can monitor extracellular Ca 2+ dynamics in rat brain, and can be completely degraded within 15 weeks. Degradable flexible electronics have broad application prospects in next‐generation wearable devices and implantable bioelectronics 11–13 …”
Section: Introductionmentioning
confidence: 99%